Pengaruh Kualitas Produk, Kualitas Pelayanan,Harga dan Brand Image terhadap Keputusan Pembelian Mie Djoedes Cabang Bence Kota Kediri - Aris Widianto; Igg Heru Marwanto; Djunaedi (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This study aimed to determine the influence of product quality, service quality, price, and brand image on purchasing decisions at Mie Djoedes Bence Branch, Kediri City. This quantitative research employed numerical data, which was analyzed using statistical methods to ensure scientific rigor. The population of this study comprised all consumers who made direct purchases at Mie Djoedes Bence Branch, Kediri City. A sample of 150 respondents was selected using nonprobability sampling. Data was collected through questionnaires and documentation. Data analysis involved validity and reliability tests, multiple linear regression analysis with a confirmatory approach. The findings revealed that: (1) Product quality had a positive and significant impact on purchasing decisions at Mie Djoedes Bence Branch, Kediri City. (2) Service quality also had a positive and significant influence on purchasing decisions. (3) Contrary to expectations, price did not significantly affect purchasing decisions at the branch. (4) Brand image exerted a positive and significant influence on purchasing decisions